A new species of Eragrostis (Poaceae, Chloridoideae) from Bolivia - Giraldo-Cañas, Diego (2023)
As a result of recent studies of South American species of Eragrostis Wolf, a new species is described. This species is endemic of a small area of the Chiquitanía Region (Bolivia). Based on IUCN criteria, the new species is categorized as “Endangered” (EN). Thus, a total of 34 species of Eragrostis are currently known in Bolivia, with two endemic species. The new species is more similar to Eragrostis airoides Nees, and therefore, their features are given.